Islamic Legal Study: Substitution of Sacrificial Animals with Money Based on The Evidences Regarding Sacrifice - Putri, Umi Muti’ah; Hasibuan, Fitri Diana; Darmawan, Fery; Arif Samudra, Bintang; Sinaga, Ali Imran (International Journal on Advanced Science, Education, and Religion, 2024)
The opinion on whether or not it is permissible to replace sacrificial animals with an amount of money equivalent to the sacrificial animal has emerged as a contemporary fiqh issue caused by the condition of society. The practice of sacrificing in this way is considered more beneficial and has many benefits for the Muslim community itself, especially in unstable economic conditions. At first glance, this opinion is an alternative and very responsive to the problems that occur. However, there is not a single argument, either in the verses of the Qur'an or the hadith of the Prophet, as well as the consensus of scholars and the MUI fatwa, which states that replacing sacrificial animals with money is permissible. The research method used is a qualitative method with a literature review approach, namely by searching for and making library materials the main source by writing, reviewing, and reducing books, scientific works, books of scholars and other literature related to the evidence for sacrifice. The results of this study indicate that based on a review of the MUI fatwa Number 37 of 2019 concerning the Preservation and Distribution of Processed Qurban Meat, and the ijma' of scholars of the four schools of thought and supporting evidence, it was decided that replacing sacrificial animals with money is not permitted because the essence of qurban is iraqah ad-dam, namely (slaughter).